Analisis Tarif Dan Besarnya Pajak Bahan Bakar Kendaraan Bermotor Di Indonesia - Setiadi Alim Lim; Lilik Indrawati (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2019)
Fossil-fueled motor vehicles play an important role in supporting the economicactivities of society. Besides having a positive effect on a country's economicgrowth, the operation of fossil-fueled motor vehicles also has a negative impact.These negative effects impose costs on society which are usually known asexternal costs and consist of air pollution costs, congestion costs, accident costs, noise costs and climate change costs. Conceptually, the external costs ofoperating these fossil fuel vehicles must be charged to motor vehicle usersthrough the imposition of various taxes, one of which can be in the form of MotorVehicle Fuel Tax. In Indonesia the Motor Vehicle Fuel Tax is levied as a RegionalTax at a rate of 5% of the Selling Value of Motor Vehicle Fuel and is notdifferentiated for petrol or diesel fuels. Research conducted shows that the MotorVehicle Fuel Tax that is collected in Indonesia is still too small, both from itsabsolute value and its tariffs, when compared with European countries, OECDand non OECD member countries and countries in the Southeast Asia Region. Inaddition, the value of the Motor Vehicle Fuel Tax collected is still insufficient to cover the external costs of operating a fossil-fueled motorized vehicle. Therefore,the tax rates for motor vehicle fuels in Indonesia must be increased and the ratesmust be separated between gasoline fuel which must be higher than diesel fuel.